Variability of HMA characteristics and its influence on pay adjustment - Praticò, Filippo Giammaria; Casciano, Antonio (Journal of Civil Engineering and Management, 2014)
The goal of this paper is to formalize and validate a model in order to determine a pay adjustment on the basis of mechanical and functional performance of transportation infrastructures. A model to determine the pay adjustment based on life expectancy of a pavement and the variability of its main properties was formulated. Five different paths and points of view are used in order to obtain information on model suitability and robustness. An algorithm has been proposed to estimate a pay adjustment (PA, negative or positive), based on life cycle cost analysis, when both structural and non-structural deficiencies/surplus in characteristics are detected. The five different methodologies, used for deriving PA, demonstrate the validity of the model in which the PA depends on both position and dispersion measures. It has been demonstrated that the model can help in analysing a project and construction management under a common framework. Analyses and validation demonstrate that the proposed model can efficiently overcome typical problems in PA determination and in contract administration, where decisions based upon objective and sound criteria are needed. Both practitioners and researchers are expected to benefit from the outcomes of this study.